WALKING SPEED OF OLDER PEOPLE AND PEDESTRIAN CROSSING TIME - Duim, E. (Innov Aging, 2017)
Decreased gait speed in older people may put them at risk of injury and social seclusion for being unable to cross streets at safe. Traffic lights consider the walking speed of 1.1 meters per second (m/s) to regulate the time for pedestrian crossing in Sao Paulo, Brazil as in New York City. However, this regulation does not consider walking speed changes across time. The objective was to assess walking speed of older people, and to compare these results with international standards for pedestrian crossing. In this cross-sectional study, the probabilistic sample of 1,191 individuals aged 60 or more years, in the city of Sao Paulo, Brazil, in 2010. Walking speed was directly assessed by a physical test, and dichotomously classified using two cut-off points: 1.1 and 0.9 m/s. Interviews informed socio-demographic and health status characteristics. A preponderant proportion (95.7%) of older adults walks at a slower pace than is currently demanded pedestrian lights (1.1 m/s). Reducing the reference speed to 0.9 m/s would allow decreasing this proportion to 69.7%. Women, brown individuals, those less schooled and those reporting poorer health status had higher odds of walking at a slower pace than would be required by traffic lights to cross streets in the city. Most older adults cannot cross streets at their own walking speed in São Paulo. These results reinforce the need of interventions targeting the whole traffic environment, to prevent accidents with older people and to promote urban mobility.